Recruitment Communication and Psychological Contracts in Start-Ups: : Dark Side Challenges of Selling a Job and Creating Realistic Expectations - Rasmussen, Mia Thyregod (Communication & Language at Work, 2020)
Recruitment communication presents a dilemma for organisations. When organisations hire, they often engage in branding themselves as employers (Backhaus & Tikoo, 2004) and rely on positive framing to present vacant positions in order to attract candidates. This leads to the ensuing challenge of living up to these promises for the candidates who are ultimately hired. Overpromising and underdelivering leads to a breach of the initial psychological contract. This balancing dilemma is especially pertinent for new and unknown companies, where concerns about the company’s legitimacy as an employer may cause potential candidates not to apply (Williamson, Cable, & Aldrich, 2002). On the one hand, start-ups need and want to attract the best, and on the other hand, they need to be wary of the impression they are creating of the job and the organisation as a place of work, as they would also like the candidates to stay once they are hired. I draw on interviews with managers and newcomers in Danish start-ups to give empirical examples of this challenge and its results, using the literature on psychological contracts (Rousseau, 1995) as an explanatory framework. I discuss what organisations might do to accomplish this balancing feat from theoretical and practical perspectives.